2002
DOI: 10.1046/j.1432-1033.2002.02981.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of bovine coagulation factor X and its glutamic‐acid‐containing fragments with phospholipid membranes

Abstract: The interaction of blood coagulation factor X and its Gla‐containing fragments with negatively charged phospholipid membranes composed of 25 mol% phosphatidylserine (PtdSer) and 75 mol% phosphatidylcholine (PtdCho) was studied by surface plasmon resonance. The binding to 100 mol% PtdCho membranes was negligible. The calcium dependence in the membrane binding was evaluated for intact bovine factor X (factor X) and the fragment containing the Gla‐domain and the N‐terminal EGF (epidermal growth factor)‐like domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
(34 reference statements)
4
11
1
Order By: Relevance
“…A nonlinear least square fit of the experimental data to a decaying exponential model (the reaction following a pseudo‐first‐order kinetics) yielded kinetic association and dissociation parameters of k a = 0.017 ± 0.007 n m −1 ·min −1 and k Da = 1.50 ± 0.22 min −1 for fX alone ( n = 3). These values are close to those reported in a recent surface plasmon resonance study of fX binding to synthetic phospholipids membranes [6], although an earlier stopped‐flow light scattering study reported two‐orders of magnitude greater values for fXa [7]. In the presence of fVIII, these parameters were changed to k a = 0.026 ± 0.012 n m −1 ·min −1 and k Da = 0.55 ± 0.04 min −1 ( n = 3) indicating a 1.5‐fold increase of the association rate and a threefold decrease of the dissociation rate.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A nonlinear least square fit of the experimental data to a decaying exponential model (the reaction following a pseudo‐first‐order kinetics) yielded kinetic association and dissociation parameters of k a = 0.017 ± 0.007 n m −1 ·min −1 and k Da = 1.50 ± 0.22 min −1 for fX alone ( n = 3). These values are close to those reported in a recent surface plasmon resonance study of fX binding to synthetic phospholipids membranes [6], although an earlier stopped‐flow light scattering study reported two‐orders of magnitude greater values for fXa [7]. In the presence of fVIII, these parameters were changed to k a = 0.026 ± 0.012 n m −1 ·min −1 and k Da = 0.55 ± 0.04 min −1 ( n = 3) indicating a 1.5‐fold increase of the association rate and a threefold decrease of the dissociation rate.…”
Section: Resultssupporting
confidence: 90%
“…Numerous studies have reported rates [6–8], equilibrium‐binding parameters [9–11], and mechanisms [12,13] for the individual binding of fIXa, fVIIIa, and fX to phospholipid membranes. Interaction of fIXa and fVIIIa within the fX‐activating complex and formation of the fIXa–fVIIIa complex have been also investigated by several groups [5,14–16], which identified interaction sites, association parameters, and contributions of different fVIIIa domains in the stimulation of the fIXa activity.…”
mentioning
confidence: 99%
“…47 Recently, the utility of BIAcore technique for evaluation of membrane-binding ability of vitamin K-dependent proteins has been demonstrated. 36,38 In the BIAcore, the K d for the QGNSEDY variant was found to be around 0.5 M, suggesting the equilibrium binding affinity to be considerably higher than that of WT protein C, which yielded a K d of 3.5 M. The corresponding values obtained in the light-scattering experiment were 2.2 M and 7.3 M, respectively. The K d values now obtained for WT protein C binding to phospholipid are in good agreement with results on record derived from light-scattering experiments.…”
Section: Discussionmentioning
confidence: 95%
“…The interaction between the protein C variants and immobilized phospholipid was also investigated using a BIAcore 2000 biosensor instrument (Biacore, Uppsala, Sweden) as described. 36 The phospholipid vesicles used for these experiments were prepared by extrusion. The phospholipid vesicles were then captured on the surface of L1 sensor chip.…”
Section: Protein Binding To Phospholipid Membranesmentioning
confidence: 99%
“…Interestingly, in this study [17], prothrombin-binding kinetics were complicated and not analysed fully, but the K D value with the DNA-tethered vesicles was estimated to be 68 nM, close to our tight-binding complex. Erb et al [24] have also studied Gla-dependent coagulation factor X (FX) binding to phospholipid membranes by SPR. Again a complex binding mechanism was observed with multiple dissociation phases, indicating multiple steps, and also some binding to pure PC membranes was reported.…”
Section: Discussionmentioning
confidence: 99%